Aloe vera based cookies as a functional food - Masood, S; Nisa, Alim un; Arif, F; Ashraf, M; Ashraf, S; Rehman, Hamood ur; Hina, S; Ahmad, I (Bangladesh Journal of Scientific and Industrial Research, 2021)
Cookies are one of the most widely consumed food products that are high in demand worldwide. Based on this fact, an attempt was made to develop the cookies by adding aloe vera gel due to its functional properties. The study was focused on the quality characterization of aloe vera-based cookies in terms of nutritional and sensory attributes. To find out the best formulation, the proximate composition and sensory analysis of biscuits containing 10%, 20% and 30% aloe vera gel were determined. For overall acceptability, cookies with 20% aloe vera gel were found best compared to the cookies containing 20% and 30% aloe vera gel. Aloe vera-based biscuits may also be helpful for most vulnerable populations in developing countries due to their functional properties. Bangladesh J. Sci. Ind. Res.56(4), 293-298, 2021